P76 Investigating women's experiences of asthma care in pregnacy: a qualitative study. (14th November 2013) - Chamberlain, C; Williamson, G R; Knight, B; Daley, M; Halpin, DM
Abstract : Introduction and objectives: Most asthmatic women have normal pregnancies and complications are infrequent when their asthma is controlled (BTS/SIGN 2012). Symptom control and medical treatment concern them, as does the impact of their illness and treatment on their unborn baby (Lim et al 2012). Few qualitative studies illustrate recently delivered asthmatic mothers' feelings about their care, support and medication during their pregnancy. The aim of the study was to investigate in a qualitative study the thoughts and feelings of women's experiences of asthma in pregnancy. Methods: NHS IRAS ethical approval and trust research governance were obtained; women gave written informed consent subject to the usual ethical guarantees. Twenty-two women with asthma and a pregnancy within two years were invited to participate. Seven women were interviewed when data saturation was achieved. Data collection took place between March 2012 and September 2012. Interviews were transcribed and analysed using a phenomenological 'Framework' Method involving familiarisation; identifying a thematic framework; indexing; charting; mapping; interpretation. Data were independently analysed by two researchers and consensus reached concerning themes. Results: Asthma and pregnancy Self-management including fears; lack of recognition of symptoms; poor knowledge of inhaled therapy Risk factors Anxieties including drugs, procedures, risks versus benefits General understanding of asthma Concealing symptoms Pregnancy and post-natal experiences: Impact of exacerbations on baby; breastfeeding benefits; changes to asthma, post-natal experience Health professionals': Lack of regular contact; midwife support; interaction with healthcare professionals, education Conclusions: These findings are globally relevant because maternal asthma is so prevalent. They illustrate participants' experiences of their asthma care and their views on its improvement. Similar to the international literature (Lim et al 2012), pregnant asthmatic women have concerns about their care and treatment, which might be alleviated by outreach, joint working between respiratory nurse specialists, midwives and GP practice nurses. References: British Thoracic Society (2012). British Guideline on the Management of Asthma. Available on-line at http://www.brit-thoracic.org.uk/Portals/0/Guidelines/AsthmaGuidelines/sign101%20Jan%202012.pdf Lim AS, Stewart K, Abramson MJ, Ryan K, George J (2012) Asthma during Pregnancy: The Experiences, Concerns and Views of Pregnant Women with Asthma. J Asthma . 49(5):474–9.